Understanding and Supporting Inhibitory Control: Unique Contributions From Proactive Monitoring and Motoric Stopping to Children's Improvements With Practice. Issue 6 (2nd August 2021) - Traut, Hilary J.; Chevalier, Nicolas; Guild, Ryan M.; Munakata, Yuko
Abstract : Children struggle to stop inappropriate behaviors. What interventions improve inhibitory control, for whom, and why? Prior work suggested that practice proactively monitoring for relevant signals improved children's inhibitory control more than practice with motoric stopping. However, these processes were not clearly dissociated. This study tested 162 seven‐ to nine‐year‐old children (89 female, 72 male, 1 unreported; 82% White) on the stop‐signal task, following monitoring or stopping‐focused practice. Both methods improved inhibitory control, supported generalization, and interacted ( η p 2  = .20–.73). Practice approaches differentially impacted variability ( η p 2  = .01–.09). Only monitoring benefits showed signs of depending upon proactive control ( η p 2  = .02). These findings highlight unique contributions of attentional and stopping processes to inhibitory control, suggesting possibilities for tailored interventions.